OC-057 The "Speedboat": a New Multi-Modality Instrument for Endoscopic Resection in the Gastrointestinal Tract. (4th June 2013) - Tsiamoulos, Z P; Hancock, C; Bourikas, L A; Sibbons, P D; Saunders, B P
Abstract : Introduction: Large sessile or flat intestinal lesions > 2 cm are optimally removed en-bloc for more accurate histology and for completeness of resection. Current submucosal dissection devices are technically challenging to use resulting in long and sometimes incomplete procedures with a high risk of major complication. We describe, for the first time, a simple to use, multi-modality endoscopic device ("Speedboat") for wide-field, en-bloc mucosal resection. Methods: The 'Speedboat' cuts in forward, lateral and oblique planes using bipolar radio frequency (RF) cutting, provides haemostasis with microwave coagulation and incorporates a retractable needle for submucosal injection and tissue irrigation. The instrument blade has an insulated 'hull' to prevent thermal injury and the device catheter is partially torque stable allowing rotation and orientation of the hull to protect the underlying muscularis propria. The electrosurgical generator is comprised of 2 power sources, one operating at 400 KHz (RF) and the other at 5.8 GHz (microwave). Speedboat submucosal dissection technique (SSD) was performed and video recorded on 3 consecutive 60 kg pigs. Mucosal areas to be resected were marked prior to submucosal injection. The mucosa was then circumferentially incised and resected by SSD. The time taken to complete resection, complications encountered and power settings used were recorded. Immediately after the procedure, the animals were euthanized, and the resection defects measured and assessed histologically. Results: Eight consecutive resections were performed (2 per animal), 7 in the colorectum and 1 in the antrum of the stomach. The median time to complete a resection was 37 minutes range (30–60 minutes) using RF cutting 24 W, voltage circa 300 Vrms. Median defect size (longest diameter) was 53.5mm, range 40–80 mm. Microwave coagulation was applied for either minor bleeding or visible vessels on 32 occasions (mean energy 7.5 W). An endoclip was used once to control arteriolar bleeding but no other haemostatic device was required. There were no perforations and histology showed an intact and viable muscle layer with some remaining submucosa in all cases. Conclusion: This initial evaluation of the "Speedboat" suggests that it facilitates rapid and safe en-bloc mucosal resection in the colorectum and gastric antrum. Disclosure of Interest: Z. Tsiamoulos Grant/Research Support from: Creo Medical Ltd, Consultancy agreement, C. Hancock Shareholder of: Creo Medical Ltd, L. Bourikas: None Declared, P. Sibbons: None Declared, B. Saunders Consultant for: Creo Medical Ltd, Consultancy and Intellectual Property agreement